Studies on Growth Performance of Local Tree Species after Coppicing - Singh, Ramesh; Singh, Th. Raghumani; Kumar, Anil (Indian Forester, 1998)
A study was conducted during 1988 to 1991 with 15 (fifteen) local multipurpose tree species for identifying maximum yield of fuelwood, fodder, pole, timber etc. about 15 years old tree species coppiced at 15 cm above the ground level at Krishnagiri Farm, Langol Hills, ICAR Research Complex for NEH Region, Manipur Centre, Imphal. The maximum height (9.46 m), girth (89.67 cm) and number of branches (19 nos.) was recorded in Grewia optiva followed by Ficus hispida, Celtis australis and Aillanthus excelsa. The maximum canopy was recorded in Ficus hispida (42.44 m2) followed by Grewia optiva and Ficus cunia. Maximum crown height was in Grewia optiva (6.69m) followed by Ficus hispida and Aillanthus excelsa. The maximum fodder (green) yield was recorded in Grewia optiva (95.5 kg/plant) followed by Ficus hispida and Bauhinia purpurea. The maximum dry matter (%) was recorded in Quercuspachyphylla (50.3%) followed by Quercusdealbata and Schimawallichii